A High Copy Number from a Pharyngeal Swab Is Not Associated with Different Presenting Features in 100 Children with Acute Adenovirus Infection from a Cluster in Italy - Anthea Mariani; Federica Cavallo; Saverio La Bella; Giusi Graziano; Martina Passarelli; Carlo Crescenzi; Daniela Trotta; Maurizio Aricò (MDPI AG, 2023)
Human mastadenoviruses, frequently denominated adenoviruses (HAdVs), may cause respiratory tract, gastrointestinal or, less frequently, other involvements. Epidemics of HAdV infections occur globally, in communities, and in closed or crowded settings. In our institution, a cluster of infants and children admitted for HAdV infection was recently observed. The aim of this study was to describe the pattern of their presenting features and investigate the possible correlation between the HAdV copy number and the clinical picture. Two main patterns of clinical presentation were observed: 68 patients had mainly respiratory symptoms (pharyngitis n = 67, cough n = 44; tonsillar exudate n = 17; other respiratory signs n = 4) while 26 patients showed prevalent gastrointestinal involvement (diarrhea n = 26, vomiting n = 8). Patients with respiratory symptoms had a significantly higher count of WBC, PMN, and platelets, while CRP level approached statistical significance (p = 0.07) for higher values in the patients with diarrhea. In order to explore the impact of selected presenting features, the possible association between the level of CRP and the presence of pharyngeal exudate, cough, vomiting, diarrhea, duration of fever, number of neutrophils, and administration of antibiotics was analyzed. Patients falling in the tertile with more elevated CRP values had tonsillar exudate and diarrhea significantly more often, while those in the lower tertile had a 4.4-day duration fever vs. ≥5.0 days in the remaining patients. Antibiotic therapy was administered more frequently to patients with higher values of CRP (p = 0.006). The duration of hospitalization was not associated with the CRP level. The median time from the receipt of a positive HAdV PCR test result to patient discharge was 1 day in 73% of cases. The number of copies of HAdV detected via PCR ranged between 47 million and 15/μL. Falling in the highest tertile of copy number was significantly associated with pharyngitis. The 24 patients with evidence of viral coinfection had no difference in the demographics or presenting features, with the only exception being a significantly higher leukocyte count. The rapid turn-around of the results of the molecular testing of the HAdV genome on a pharyngeal swab allowed us to rapidly diagnose HAdV infection, allowing us to stop antibiotic therapy and immediately discharge the patients, with reduced discomfort for the families and more appropriate use of hospital beds. A high copy number of HAdV from a pharyngeal swab should not be taken as an indicator of worse prognosis, thus allowing for the preferential use of qualitative rather than quantitative assay.